Objective Recognition of Tinnitus Location Using Electroencephalography Connectivity Features - Li, Zhaobo; Wang, Xinzui; Shen, Weidong; Yang, Shiming; Zhao, David Y.; Hu, Jimin; Wang, Dawei; Liu, Juan; Xin, Haibing; Zhang, Yalun; Li, Pengfei; Zhang, Bing; et al. (Frontiers in Neuroscience, 2022)
Purpose: Tinnitus is a common but obscure auditory disease to be studied. This study to determine whether the connectivity features in EEG signals can be used as the biomarkers for an efficient and fast diagnosis method for chronic tinnitus. Methods: In this study, the resting-state EEG signals of tinnitus patients with different tinnitus locations were recorded. Four connectivity features (including the Phase-locking value (PLV), Phase lag index (PLI), Pearson correlation coefficient (PCC), and Transfer entropy (TE)) and two time-frequency domain features in the EEG signals were extracted, and four machine learning algorithms, included two support vector machine models (SVM), a multi-layer perception network (MLP) and a convolutional neural network (CNN), were used based on the selected features to classify different possible tinnitus sources. Results: Classification accuracy was highest when the SVM algorithm or the MLP algorithm was applied to the PCC feature sets, achieving final average classification accuracies of 99.42 % or 99.1 %, respectively. And based on the PLV feature, the classification result was also particularly good. And MLP ran the fastest, with an average computing time of only 4.2 seconds, which was more suitable than other methods when a real-time diagnosis was required. Conclusions: Connectivity features of the resting-state EEG signals could characterize the differentiation of tinnitus location. The connectivity features (PCC and PLV) were more suitable as the biomarkers for the objective diagnosing of tinnitus. And the results were helpful for clinicians in the initial diagnosis of tinnitus.